Juvenile justice in African and Western criminal justice systems - Sungi, Simeon P.; Kakoti, George Rugaimukamu; Christian, Deneil D. (Information Science Reference, 2023)
"This book intends to provide a comprehensive introduction to the field of juvenile justice from a comparative perspective between African and Western criminal justice systems. Most African jurisdictions inherited the juvenile justice systems from colonial governments, and many of these African jurisdictions still maintain the colonial structure in dealing with juvenile offenders. It is designed to help readers understand the complexities of the present juvenile justice practice by presenting in a comparative perspective, a thorough examination of the social, historical, and legal context within which delinquency and juvenile justice practice occur"--